Computational Fluid Dynamics and Experimental Hydrodynamic Analysis of a Solar AUV - Asadi Asrami, Ehsan; Moonesun, Mohammad; Azizi Abi, Farhad (Computer Assisted Methods in Engineering and Science, 2021)
In the present study, the effect of free surface on the hydrodynamic forces acting on the motion of an autonomous underwater vehicle (AUV) has been investigated. The AUV is powered by solar energy. Using computational fluid dynamics, the Reynolds averaged Navier Stokes (RANS) equations for the flow around the AUV are solved, and the free surface effect is simulated using the volume of fluid (VOF) two-phase flow model. For this purpose, the commercial code ANSYS FLUENT 18 was used. The results of the numerical solution are compared with experimental results of the AUV model in the surface motion in the towing tank of the Persian Gulf National Laboratory with a scale of 1:1. The experiment was performed in a fixed draft and the velocity was ranging from 0.2 m/s to 1.4 m/s (according to Reynolds number 2.4 x 105 to 1.7 x 106).